Vaccination with parasite-specific TcTASV proteins combined with recombinant baculovirus as a delivery platform protects against acute and chronic Trypanosoma cruzi infection - Masip, Yamil E.; Caeiro, Lucas D.; Cosenza, Maximiliano; Postan, Miriam; Molina, Guido; Taboga, Oscar; Molinari, María Paula; Tekiel, Valeria (Frontiers in Cellular and Infection Microbiology, 2024)
Chagas' is a neglected disease caused by the eukaryotic kinetoplastid parasite, Trypanosoma cruzi. Currently, approximately 8 million people are infected worldwide, most of whom are in the chronic phase of the disease, which involves cardiac, digestive, or neurologic manifestations. There is an urgent need for a vaccine because treatments are only effective in the initial phase of infection, which is generally underdiagnosed. The selection and combination of antigens, adjuvants, and delivery platforms for vaccine formulations should be designed to trigger mixed humoral and cellular immune responses, considering that T. cruzi has a complex life cycle with both intracellular and bloodstream circulating parasite stages in vertebrate hosts. Here, we report the effectiveness of vaccination with a T. cruzi-specific protein family (TcTASV), employing both recombinant proteins with aluminum hydroxide and a recombinant baculovirus displaying a TcTASV antigen at the capsid. Vaccination stimulated immunological responses by producing lytic antibodies and antigen-specific CD4+ and CD8+ IFNɣ secreting lymphocytes. More than 90% of vaccinated animals survived after lethal challenges with T. cruzi, whereas all control mice died before 30 days post-infection. Vaccination also induced a strong decrease in chronic tissue parasitism and generated immunological memory that allowed vaccinated and infected animals to control both the reactivation of the infection after immunosuppression and a second challenge with T. cruzi. Interestingly, inoculation with wild-type baculovirus partially protected the mice against T. cruzi. In brief, we demonstrated for the first time that the combination of the baculovirus platform and the TcTASV family provides effective protection against Trypanosoma cruzi, which is a promising vaccine for Chagas disease.